Bora Laskin : bringing law to life - Girard, Philip; Osgoode Society for Canadian Legal History (Toronto [Ont.] : Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2005)
In Bora Laskin, Girard chronicles the life of a man who, at all points of his life, was a fighter for a better Canada: he fought antisemitism, corporate capital, omnipotent university boards, the Law Society of Upper Canada, and his own judicial colleagues in an effort to modernize institutions and re-shape Canadian law.
""19 The Laskin Court""""20 The Great Dissenter""; ""21 Architect of Public Law""; ""22 Patriation""; ""23 The Berger Affair""; ""24 Final Years""; ""25 Epilogue""; ""NOTES""; ""ILLUSTRATION CREDITS""; ""INDEX""; ""A""; ""B""; ""C""; ""D""; ""E""; ""F""; ""G""; ""H""; ""I""; ""J""; ""K""; ""L""; ""M""; ""N""; ""O""; ""P""; ""Q""; ""R""; ""S""; ""T""; ""U""; ""V""; ""W""; ""Y""; ""Z""
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Laskin, Bora; Canada. -- Supreme Court -- Biography; Laskin, Bora; Canada. -- Cour suprême -- Biographies; Laskin, Bora; Canada. -- Supreme Court; Judges -- Canada -- Biography; Juges -- Canada -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Lawyers & Judges; LAW -- Civil Procedure; LAW -- Legal Services; POLITICAL SCIENCE -- Government -- Judicial Branch; LAW -- Legal History; Judges; Canada; Electronic books; Biographies